The Influence of Customer Loyalty And Interest Buy Against Sales Target Pt Sinar Rezekimas Makmur - Kelvin Alwendo; Thomas Sumarsan Goh; Wily Julitawaty; Syawaluddin (Enrichment : Journal of Management, 2022)
The sales target is the value to be achieved when the business is doing marketing. Customer loyalty is evidence of consumer loyalty to use a product or service continuously because having high satisfaction with the product or service to be used will tend to arise to recommend products or services to other potential customers. Buying interest is a desire to buy a product or service due to both external and internal influences where previously an evaluation of the product or service to be purchased was carried out. This type of research is descriptive quantitative. The data analysis technique used is multiple regression analysis, partial test, simultaneous test and coefficient of determination test. The measurement scale uses a Likert scale. The results of the study partially proved that customer loyalty had a significant positive effect on the sales target of PT Sinar Rezekimas Makmur. The results of the study partially proved that buying interest had a significant positive effect on the sales target of PT Sinar Rezekimas Makmur. The results of the study simultaneously proved that customer loyalty and buying interest had an effect on the sales target of PT Sinar Rezekimas Makmur